Communication sounds of Commerson's dolphins (Cephalorhynchus commersonii) and contextual use of vocalizations. Issue 4 (20th May 2016) - Reyes Reyes, M. Vanesa; Tossenberger, Vanesa P.; Iñiguez, Miguel A.; Hildebrand, John A.; Melcón, Mariana L.
Abstract: Cetaceans produce a variety of vocalizations to communicate; however, little information exists on the acoustic behavior displayed by Commerson's dolphins ( Cephalorhynchus commersonii ) in the wild other than their echolocation behavior. Most available literature suggests that Commerson's dolphins do not produce any other sound type besides narrow‐band high‐frequency (NBHF) clicks, such that no signals are emitted below 100 kHz. We conducted acoustic recordings together with sightings to study the acoustic behavior of Commerson's dolphins in Bahia San Julian, Argentina. This is the first study that provides evidence that this species produces a variety of acoustic signals, including whistles and broad‐band clicks (BBC), with frequency content well below 100 kHz. Whistles were recorded mostly in the presence of mother and calf and were associated with parental behavior. BBC may be used for communication purposes by adults. These vocalizations are within the hearing range of killer whales and so could pose a risk of predation for Commerson's dolphins. Whether this population of Commerson's dolphins produce all these types of signals while they are in the open sea out of the waters of Bahía San Julián, which are apparently safe from predation, remains unknown.